Economic theory and policy Essays in honour of Dipak Banerjee - Dutta, Bhaskar; Moodherjee, Dilip; Gangopadhyay, Shubhasahis; Dutta, Bhaskar (Mumbai Oxford University Press, 1990)
Macro economic and policy